Position paper on the use of an "estimated acceptable concentration" (EAC) as basis for a control policy's action level for carcinogens unintentionally present in food. (January 2021) - Claeys, Wendie; De Meulenaer, Bruno; De Saeger, Sarah; Matthys, Christophe; Pussemier, Luc; Rajkovic, Andreja; Scippo, Marie-Louise; Vleminckx, Christiane; Van Huffel, Xavier; Hoet, Peter
Abstract: Background: In the absence of legal maximum limits, the competent authority may act if high contamination levels that endanger public health are identified. A pragmatic approach to identify whether a value is potentially too high, is to set action levels which, if exceeded, call for action involving a notification, withdrawal of the food from the market, legal measures or an investigation. Scope and approach: As control policy's action levels should be considered as part of risk management, which is not always based on scientific risk assessment alone, the concept of an 'estimated acceptable concentration' (EAC) is introduced. The EAC is defined as a risk-based level of a substance in a food below which the exposure to the substance via the food does not pose a concern or a risk for public health. This EAC concept is substantiated by a quick scoping review of scientific literature and reports. Key findings and conclusions: Case-dependent, whether a threshold effect level can be defined or not, the EAC is calculated based on the health-based guidance value or the margin of exposure (MOE) approach. It can serve as a basis for a food safety management action level, allowing food inspectors to take uniform actions and providing clarity to food business operators. Application of the EAC should be viewed in the appropriate framework, including consideration of the tolerable risk level and uncertainties. Although the presented concept addresses exposure to an individual substance from a single source, the combined exposure to multiple chemicals and exposome can be included. Highlights: Adoption of pragmatic action levels allowing uniform policy measures and clarity for operators in absence of legal limits. Action levels based on an 'estimated acceptable concentration' (EAC). Derivation of the EAC using the margin of exposure (MOE) approach. Toxic potency and exposure assessment uncertainties should be born in mind. Mainly individual substances are addressed, but mixtures and exposome can be included.